Análise genética e da estratégia de ocupação das populações de Egeria (Hydrocharitaceae) da bacia do alto rio Paraná. - Lucio, Léia Carolina (2009)
Egeria densa and Egeria najas (Hydrocharitaceae) are native species from the Upper Paraná River Basin (Brazil). They colonize a variety of ecosystems and are characterized by having an intense flow of propagules within and between environments. The main goals of this thesis were to: (i) assess the genetic diversity of Egeria populations, (ii) use markers corresponding to the trnL partial sequence and to trnL-trnF intergenic spacer from the cpDNA and ITS region of rDNA to molecularly characterize E. densa and E. najas populations; and (iii) isolate microsatellites region to design primers that flank SSR regions for Egeria densa. The low genetic diversity of both E. densa and E. najas populations, observed using dominant molecular markers, indicates a predominance of vegetative reproduction. However, this observation does not discard completely the presence of sexual reproduction. The characterization of nucleotide sequences from both chloroplastidic and nuclear genomes identified distinct haplotypes in both species. However, only the nuclear genome (corresponding to the ITS region of rDNA) allowed the discrimination of different haplotypes and was useful to molecularly characterize E. densa and E. najas. Moreover, one of the haplotype combinations may indicate that genetic recombination is present, although rare. Codominantes molecular markers, such as microsatellites (SSR), generated higher polymorphism and were more successful to evaluate the genetic diversity of Egeria populations. However, few SSR primers are currently described for aquatic vegetation. The isolation and development of these primers were completed in our study, with future prospects for their employment. Genetic analyses of Egeria populations are useful to understand the occupation strategy of the environments of the Upper Paraná River basin. The migration processes of vegetative fragments and the low genetic variability of individuals, which increases with distance among patches, suggests that Egeria populations follow a Metapopulation dynamics. Microsatellite markers were more efficient than the dominant markers and support more conclusive investigations about the genetics and occupancy of native populations of E. densa and E. najas in the Upper Paraná River basin.